Integrasi Ekosistem Bisnis dan Kesadaran Lingkungan dalam Perspektif Akuntansi Keberlanjutan: Bukti pada Keberlanjutan Usaha Petani Karet Perempuan - Sahara, Sahara; Heriyani, Heriyani; Chilmatussa'adah, Chilmatussa'adah (Magister Ilmu Akuntansi Universitas Jambi, 2026)
This study aims to analyze the effects of business ecosystems and environmental awareness on the business sustainability of women rubber farmers, using a sustainability accounting perspective to interpret the research findings. This research employs a quantitative approach using primary data collected through questionnaires distributed to women rubber farmers in Karang Sari Hamlet, Jambi Province. The data analysis technique used is multiple linear regression with the assistance of IBM SPSS, including t-tests and F-tests. The results indicate that environmental awareness has a positive and significant effect on business sustainability, whereas the business ecosystem has no significant partial effect. However, both variables simultaneously influence business sustainability. Based on the sustainability accounting perspective, these findings indicate that environmental awareness plays a role in improving cost efficiency and optimizing resource management, thereby supporting long-term business sustainability. This study highlights the importance of integrating environmental aspects into business decision-making as part of sustainability accounting practices in small-scale agricultural sectors.